Dose-Response Effect of Elevated Plasma Free Fatty Acid on Insulin Signaling - Belfort, Renata; Mandarino, Lawrence; Kashyap, Sangeeta; Wirfel, Kelly; Pratipanawatr, Thongchai; Berria, Rachele; DeFronzo, Ralph A.; Cusi, Kenneth (Diabetes (New York, N.Y.), 2005)
Dose-Response Effect of Elevated Plasma Free Fatty Acid on Insulin Signaling Renata Belfort 1 , Lawrence Mandarino 1 2 3 , Sangeeta Kashyap 1 , Kelly Wirfel 1 , Thongchai Pratipanawatr 1 , Rachele Berria 1 , Ralph A. DeFronzo 1 4 and Kenneth Cusi 1 4 1 Diabetes Division, Department of Medicine, the University of Texas Health Science Center at San Antonio, San Antonio, Texas 2 Diabetes Division, Department of Biochemistry, the University of Texas Health Science Center at San Antonio, San Antonio, Texas 3 Diabetes Division, Department of Physiology, the University of Texas Health Science Center at San Antonio, San Antonio, Texas 4 Audie L. Murphy Veterans Administration Medical Center, San Antonio, Texas Address correspondence and reprint requests to Kenneth Cusi, MD, University of Texas Health Science Center at San Antonio, Diabetes Division, 7703 Floyd Curl Dr., San Antonio, TX 78229. E-mail: cusiatuthscsa.edu Abstract The dose-response relationship between elevated plasma free fatty acid (FFA) levels and impaired insulin-mediated glucose disposal and insulin signaling was examined in 21 lean, healthy, normal glucose-tolerant subjects. Following a 4-h saline or Liposyn infusion at 30 ( n = 9), 60 ( n = 6), and 90 ( n = 6) ml/h, subjects received a 2-h euglycemic insulin (40 mU · m −2 · min −1 ) clamp. Basal plasma FFA concentration (∼440 μmol/l) was increased to 695, 1,251, and 1,688 μmol/l after 4 h of Liposyn infusion and resulted in a dose-dependent reduction in insulin-stimulated glucose disposal ( R d ) by 22, 30, and 34%, respectively (all P < 0.05 vs. saline control). At the lowest lipid infusion rate (30 ml/h), insulin receptor and insulin receptor substrate (IRS)-1 tyrosine phosphorylation, phosphatidylinositol (PI) 3-kinase activity associated with IRS-1, and Akt serine phosphorylation were all significantly impaired ( P < 0.05–0.01). The highest lipid infusion rate (90 ml/h) caused a further significant reduction in all insulin signaling events compared with the low-dose lipid infusion ( P < 0.05–0.01) whereas the 60-ml/h lipid infusion caused an intermediate reduction in insulin signaling. However, about two-thirds of the maximal inhibition of insulin-stimulated glucose disposal already occurred at the rather modest increase in plasma FFA induced by the low-dose (30-ml/h) lipid infusion. Insulin-stimulated glucose disposal was inversely correlated with both the plasma FFA concentration after 4 h of lipid infusion ( r = −0.50, P = 0.001) and the plasma FFA level during the last 30 min of the insulin clamp ( r = −0.54, P < 0.001). PI 3-kinase activity associated with IRS-1 correlated with insulin-stimulated glucose disposal ( r = 0.45, P < 0.01) and inversely with both the plasma FFA concentration after 4 h of lipid infusion ( r = −0.39, P = 0.01) and during the last 30 min of the insulin clamp ( r = −0.43, P < 0.01). In summary, in skeletal muscle of lean, healthy subjects, a progressive increase in plasma FFA causes a dose-dependent inhibition of insulin-stimulated glucose disposal and insulin signaling. The inhibitory effect of plasma FFA was already significant following a rather modest increase in plasma FFA and develops at concentrations that are well within the physiological range (i.e., at plasma FFA levels observed in obesity and type 2 diabetes). CRC, Clinical Research Center EGP, endogenous glucose production FFA, free fatty acid G6P, glucose-6-phosphate IRS, insulin receptor substrate PI, phosphatidylinositol Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “ advertisement ” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted March 2, 2005. Received October 9, 2004. DIABETES